Field Study: In Health Centers and Hospitals, Infection Control and Awareness of Workers in All Specialties - ALGHAMDI , ALI AHMED; Aljubran, Hawraa Ali Mohammed; ALSHURAYYAN, MANA DHAFIR MOHAMMED; al yami, Ghazi mohammd hassan; Al abdullah, Marzoug Ali Mohd; Al Johani , Yasser Mohammed; Alshehri, Nasser Mohammed; Sabrah , Saad Ali; Alsagoor, Mohammad Mani Hussen; Alsharyh, Mohammad mahdi hamad; Alsharyh, Mohammad Ali Mahdi; SAEED, GHADA YAHIA (Journal of Ecohumanism, 2024)
This field study worked in hospitals and health centers to activate infection control standards in health facilities, and the importance of applying them to workers in health facilities even after health centers obtained the accreditation certificate for quality standards in health facilities (CPAHI). The questionnaire was created and sent electronically via social media, where 700 social questionnaires were distributed to people aged (23-58 years), men and women in the city Of Riyadh, and responses from 450 people were obtained via Google Drive.it is concluded the rate Of application Of infection control standards is high.